THE “STATEHOOD” OF THE HOLY SEE AND THE CIVIL JURISDICTIONAL IMMUNITY: THE JUDGEMENT OF THE EUROPEAN COURT OF HUMAN RIGHTS - Alemanno, Giorgia (Revista da Faculdade de Direito do Sul de Minas, 2022)
Holy See’s role, in an international level, has always been a very controversial issue due to the strict relationship with the Vatican City State. The European Court of Human Rights third section’s judgement of October 12th, 2021, represents a real innovation in the international framework as thirty-nine people of different nationalities, reported some representatives of the Belgian Catholic Church for sexual abuses. The applicants filed an appeal for the alleged violation of article 6 ECHR against the Holy See which acts, on one hand, as the beating heart of the Vatican City State and the Catholic Church, and, on the other, as the Pope’s moral representation.